PENERAPAN PEMBELAJARAN “WISATA LOKAL” MELALUI WEB SEBAGAI UPAYA PENINGKATAN RESPON DAN HASIL BELAJAR 1 MATEMATIKA SISWA DI SMKN 1 SUMBERREJO - Sriatun Sriatun (Universitas Muhammadiyah Semarang, 2017)
Education Unit Level Curriculum requires students to be active and cooperatewith other students, in the implementation of learning indicate the existence ofdeficiency, One of them still rarely asks students, and if asked by the teacherlooks student hesitate and afraid to reply.In addition in the end hours studentsfeel lazy in follow teaching and learning activities.This study aims to improve student responses and mathematics learningoutcomes on statistical materials. This type of research is a classroom actionresearch. The research was conducted in class XII of SMKN 1 SumberrejoBojonegoro.Student response data obtained from the observation and recording of handycam at the time of student group discussion of learning result data obtained from post test assessment. Keywords: Learning